PENGARUH SUHU DAN LAMA DISTILASI TERHADAP RENDEMEN DAN KARAKTERISTIK DISTILAT ALKOHOL DARI CAIRAN PULPA HASIL SAMPING FERMENTASI BIJI KAKAO. - Anggakara Putra, I Gusti Gde Satria; Wartini, Ni Made; Wrasiati, Ni Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
The aims of this study were to 1) determine the influence of temperature and time of distillation of the alcohol distillate characteristics of watery sweating, 2) obtain the temperature and time of distillation is capable to producing the best characteristics of the alcohol distillate of watery sweating. This study consist of two factors, using a randomized block design. The first factor was a time of distillation which consists of 4 levels, namely 15, 30, 45 and 60 minutes. The second factor was the temperature of distillation which consists of 2 levels namely 90±2°C and 100±2°C. The experiments are grouped into 2 groups based on the time of implementation, thus obtained 16 experimental units. Variables observed that the yield, alcohol content, pH, total acid and total dissolved solids. Temperature of 90±2°C and 15 minutes time of distillation was an appropriate treatment to produce alcohol from the watery sweating with the best characteristics that yield of 1.5 %, 30.99 % alcohol content, acidity (pH) 3.48, total acid 0.0307 meq NaOH/g and total dissolved solids 11.6 % Brix. Keywords: watery sweating, fermentation, distillation, alcohol.
Keywords: 61